Growth of Legionella pneumophila in Acanthamoeba castellanii enhances invasion. - Cirillo, J D (1994)
Legionella pneumophila is considered to be a facultative intracellular parasite. Therefore, the ability of these bacteria to enter, i.e., invade, eukaryotic cells is expected to be a key pathogenic determinant. We compared the invasive ability of bacteria grown under standard laboratory conditions with that of bacteria grown in Acanthamoeba castellanii, one of the protozoan species that serves as a natural host for L. pneumophila in the environment. Amoeba-grown L. pneumophila cells were found to be at least 100-fold more invasive for epithelial cells and 10-fold more invasive for macrophages and A. castellanii than were L. pneumophila cells grown on agar. Comparison of agar- and amoeba-grown L. pneumophila cells by light and electron microscopy demonstrated dramatic differences in the morphology and structure of the bacteria. Analyses of protein expression in the two strains of bacteria suggest that these phenotypic differences may be due to the expression of new proteins in amoeba-grown L. pneumophila cells. In addition, the amoeba-grown bacteria were found to enter macrophages via coiling phagocytosis at a higher frequency than agar-grown bacteria did. Replication of L. pneumophila in protozoans present in domestic water supplies may be necessary to produce bacteria that are competent to enter mammalian cells and produce human disease.